1990
DOI: 10.1002/pen.760300907
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical fracture behavior of polyacetal and thermoplastic polyurethane elastomer toughened polyacetal

Abstract: Polyacetal (POM) toughening with thermoplastic polyurethane (TPU) elastomer was investigated in terms of Theological, mechanical, and morphological properties. Polyacetal can be effectively toughened by the blending with TPU elastomer and the improvement on toughness is found most significant with TPU content from 20 to 30 percent. POM does fracture in ductile mode under extremely low deformation rate and the ductile‐brittle transition rate is at 0.5 mm/min. The transition rate is increased with the increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 12 publications
0
44
0
Order By: Relevance
“…POM samples prepared by cooling from the melt exhibits the ECC bands more clearly, allowing to speculate that the POM sample crystallized from the melt is a mixture of ECC and FCC in a complicated manner. It was assumed that lamellar stacking structure formed in the temperature region I (primary crystallization) becomes tighter in the temperature region II (secondary crystallization) by a generation of second lamellae in between the original lamellae [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…POM samples prepared by cooling from the melt exhibits the ECC bands more clearly, allowing to speculate that the POM sample crystallized from the melt is a mixture of ECC and FCC in a complicated manner. It was assumed that lamellar stacking structure formed in the temperature region I (primary crystallization) becomes tighter in the temperature region II (secondary crystallization) by a generation of second lamellae in between the original lamellae [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers [1][2][3][4][5][6][7][8][9][10][11][12][13] investigated the toughened POM/TPU blends focusing on physical properties, fracture behavior, and toughening mechanism. It was reported that the toughness of the POM/TPU blends depend on the concentration of TPU, [2][3][4]6,8,9,11 the interparticle distance of dispersed TPU phase 10,13 and the compatibility between POM and TPU. 12,13 With reagard to compatibilizers for the POM/TPU blends, Mehrabzadeh et al reported that 3% of diphenylmethane diisocyanate (MDI) in the POM/TPU (85/15 by weight) blend reduced the particle size of TPU and achieved the maximum impact strength, 12 and Gao et al reported that polystyrene-block-poly(ethylene-butylene)-block-polystyrene grafted with maleic anhydride (SEBS-graft-MA) enhanced the interfacial interaction between POM and TPU.…”
Section: Introductionmentioning
confidence: 99%
“…The blend AU73 exhibits a 150% increment in impact strength, and this observation is in consonance with that of Chang et a1. 12 who have made studies with POM blends containing up to 30% TPU. It appears that addition of TPU exceeding 30% TPU does not improve the impact strength but decreases it.…”
Section: Resultsmentioning
confidence: 99%